From principle to practice? The resilience–local ownership nexus in the EU Eastern Partnership policy. Issue 2 (2nd April 2020) - Petrova, Irina; Delcour, Laure
ABSTRACT: By emphasizing concepts such as resilience and local ownership, recent updates in the EU's foreign policy strategy have marked a narrative turn and signaled a shift in EU external governance toward its neighborhood. This article has two aims. First, we unpack the EU's conceptual understanding of resilience and local ownership as reflected in its recent strategic documents. Second, we examine the implications of the EU's narrative turn on actual policy practices in Eastern Partnership countries. We highlight a gap between the EU's broad understanding of resilience and local ownership and the narrow operationalization of these concepts in the EU's eastern policy. The article shows that the EU continued relying on the previously established policy frameworks, according to which resilience develops through approximation with EU templates. This strong path dependence precluded any effective policy turn toward local ownership.